SELECTION OF RATIONAL PARAMETERS OF THE NOMINAL MODE OF ELECTRIC LOCOMOTIVES - Hetman, H. K.; Marikutsa, S. L. (Science and Transport Progress, 2017)
Purpose.The railways of Ukraine have been operated the locomotives, which are both morally and physically obsolete. Therefore, to ensure the competitiveness of rail transport it is necessary to update the locomotive fleet, and first of all the fleet of electric locomotives, because electrified railways provide the greater part of passenger and freight traffic. In this connection it is of special importance to determine the optimum parameters of the nominal mode of electric rolling stock. The purpose of the work is to examine the features of solution of these problems with respect to electric locomotives. Methodology. Assuming that the limit values of traction force are determined by the conditions of wheel-rail grip, then the power of the nominal mode can be represented as the product of rated speed, estimated friction coefficient, train weight and the coefficients that represent the ratio of the estimated (starting) value of traction force to value of traction force the nominal mode and the ratio of the mass of the locomotive to the train weight. Since the mass of the train is not a constant value, there is always a surplus power of the locomotive fleet required for the mastering of a predetermined volume of transportations. Reduced overcapacity of the locomotive fleet can be achieved by introduction of the locomotives of different power, designed for driving trains of different weight that will result in increased completeness of the power use but also in difficulty in selecting of locomotives for trains in operation. The paper shows the method of calculating the optimum values of power, speed and traction force of the nominal mode. It presents the mathematical model of the relationship of traction rate, excessive capacity and power of the traction unit. Findings.It is proved that the power of the traction unit, the total fleet power requirement and the excess of power in absolute units are proportional to the speed of the nominal mode. To reduce the total power of the fleet when selecting the optimum power of the traction unit it is necessary to take into consideration the speed of the nominal mode, defined by the condition of minimization of power consumption for traction, i.e. the smallest value that enables the implementation of the given running speed and the powerredundancy level required for operation. Originality. It consists in the development of a unified algorithm for determining the optimal parameter values of the nominal mode of passenger, freight and freight-passenger electric locomotives. Practical value. The authors determined the minimization costs during production, acquisition and maintenance of electric locomotives, whose nominal mode parameters are designed according to the above procedure.